2022
DOI: 10.1101/2022.12.01.518666
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arabidopsis hydathodes are sites of intense auxin metabolism and nutrient scavenging

Abstract: Hydathodes are small organs located on the leaf margins of all vascular plants. They release excess xylem sap through guttation when stomata are closed or when the humidity level is high. Many promoter analyses have suggested other hydathode functions in metabolite transport and auxin metabolism, but experimental demonstration is still lacking. Here, we compared the transcriptomic and metabolomic features of mature Arabidopsis hydathodes to the leaf blade. 1460 differentially-expressed genes were identified re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 102 publications
2
9
0
Order By: Relevance
“…Reconstruction of transversal sections revealed that PIN1 is preferentially expressed at the adaxial side of the leaf vasculature (Figure 3j). PIN1 transcripts were also detected in hydathodes, in agreement with transcriptomic analysis (Routaboul et al ., 2022) (Figure 3o-p), and at the tip of nascent serrations at the leaf margin (Figure 3l, n) (Bilsborough et al ., 2011). To our knowledge, this is the first time PIN1 transcripts was detected using WISH.…”
Section: Resultssupporting
confidence: 87%
“…Reconstruction of transversal sections revealed that PIN1 is preferentially expressed at the adaxial side of the leaf vasculature (Figure 3j). PIN1 transcripts were also detected in hydathodes, in agreement with transcriptomic analysis (Routaboul et al ., 2022) (Figure 3o-p), and at the tip of nascent serrations at the leaf margin (Figure 3l, n) (Bilsborough et al ., 2011). To our knowledge, this is the first time PIN1 transcripts was detected using WISH.…”
Section: Resultssupporting
confidence: 87%
“… (B) Cluster-specific expression profiles of cell-type marker genes. The marker genes were selected from the literature ( Kim et al., 2021 ; Routaboul et al., 2022 ; Tenorio Berrío et al., 2022 ). GC, CC, EC, HC, MC, and SC stand for guard cells, companion cells, epidermal cells, hydathode cells, mesophyll cells, and vascular S cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Hydathodes are specialized organs that prevent the harmful effect of excess water and xylem sap [ 25 , 26 , 27 ]. Moreover, hydathodes are the auxin biosynthesis gene reservoir [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ], while auxin has been observed in hydathodes via immunolocalization [ 29 ].…”
Section: Resultsmentioning
confidence: 99%